Confocal laser endomicroscopy for in vivo detection of gastric intestinal metaplasia: a randomized controlled trial - Li, Zhen; Zuo, Xiu-Li; Yu, Tao; Gu, Xiao-Meng; Zhou, Cheng-Jun; Li, Chang-Qing; Ji, Rui; Li, Yan-Qing (Endoscopy, 2014)
Background and study aims: Gastric intestinal metaplasia (GIM) is associated with a risk for development of intestinal-type gastric cancer. This study aimed to compare the diagnostic yield of GIM from confocal laser endomicroscopy (CLE) and white light endoscopy (WLE). Patients and methods: In a prospective, double-blind, randomized study, patients were randomly assigned to receive either CLE with targeted biopsies (group A) or WLE with a standard biopsy protocol (group B). Results: A total of 168 patients were finally analyzed (group A 85, group B 83). On a per-patient analysis, the diagnostic yields of GIM (including GIM with gastric intraepithelial neoplasia [GIN]) for groups A and B were 44.71 % and 31.33 %, respectively (P = 0.074). On a per-biopsy analysis, CLE-targeted biopsy gave a significantly higher diagnostic yield of GIM compared with WLE and standard biopsy, at 65.70 % (113 /172 biopsies) versus 15.73 % (81 /515 biopsies) (P < 0.001). Moreover, the diagnostic yield of the operative link on gastric intestinal metaplasia (OLGIM) assessment stages III and IV was higher at 20.93 % (36 /172 biopsies) in group A versus 4.08 % (21 /515 biopsies) in group B (P < 0.001). In addition, use of CLE-guided biopsy significantly decreased by 68 % (P < 0.001) the mean number of biopsies required per patient. Conclusions: CLE with targeted biopsies is superior to WLE with standard biopsies for the detection and surveillance of GIM. The number of biopsies needed to confirm GIM is about one third of that needed with WLE with standard biopsies.